Ram Thap Yao Folk Dance Of Nakhon Si Thammarat - Panasri, Chotika; Jongda, Surat; Wangwon, Suksanti (Mahachula Academic Journal, 2025)
The objectives of this research work were (1) to study on the history, origins, patterns, and components of the Thap Yao Dance (Dance to Long Drum) Performance in Nakhon Si Thammarat Province, and (2) to analyze the components of four Thap Yao Flok dances in Nakhon Si Thammarat Province of 4 Thap Yao (Long Drum) Bands, namely, Thadee Sunthonsilp Band from Lan Saka District, Nakhon Si Thammarat Province; Na Mai Pai Band from Thung Song District, Nakhon Si Thammarat Province; Luk Mae Chao Yu Hua Band from Chian Yai District, Nakhon Si Thammarat Province; and Nai Pim Amornchon’s Band from Mueang District, Nakhon Si Thammarat Province. Data were collected from documents,relevant researchworks, participatory observation, and interviews with academics, performers, and general informants. The data were compiled and analyzed with the results presented with the analytical descriptive technique. The research findings showed that Thap Yao Dance Performance of Nakhon Si Thammarat Province was adapted from Ram Klong Yao (Long Drum Dance) Performance that was invented by the Fine Arts Department, with combination with the southern Thai musical instrument or Thap (Drum). However, the performance has been designed to have fancier pattern than the original version. Thap Yao (Southern Long Drum) is always played along with the in the shadow puppet (Nang Talung) and Nora (dance imitating gestures of a Mythical Creature that is a half woman and half bird creature) performances. The Thap Yao Dance uses Nora postures, which people in Nakhon Si Thammarat Province are skilled at because it is a popular folk performance. The dance patterns weee divided into 3 phases. Phase 1 was the Wai Khru Dance (Dance Commemorating Maestros).Phase 2 was the dance to the rhythm of the music, depending on each band. However, in general, this phase consisted of 12 songs in total. Phases 3 was the final part of the Thap Yao Flok Dance. The entire band will adhere to the same practice, ending with the Hak Kor Ai Teng song. The dance posture would be a Nora posture called Tha Nat. This Tha Nat posture is similar to the Ram Sai (Swaying Dance) posture of Thai classical dance, whether it was the swaying dance with one hand on one side or the dance with both hands, which were seen in Nora Performance as well. As for the costumes for the Thap Yao Dance Performance of Nakhon Si Thammarat Province, three styles of costumes were discovered. The first style consisted of a knee-length sarong like the Soeng Dance (Northeastern Thai Dance) Performance, with a round-necked shirt with long sleeves and a front slit. The second style consisted of a pair of trousers or a Chong Kra Ben (trousers like outfits created from a piece of cloth or ready-to-wear capris), with a round-necked shirt and loin cloths tied at the head and the waist. The third style consisted of a modern ready-to-wear wrap-around skirt with a round-necked shirt with long sleeves. The unique component of all the three styles of costumes that has not changed was a cloth slung across the body and over the shoulder (Sabai). The musical instruments used included Thap Yao (long drums), Nora pipes, a gong, cymbals, and bamboo castanets. In more modern eras, more musical instruments such as quadruple drum, cup-shaped cymbals and keyboard were added.